Concept Attainment in Geometry through CLD Model among Class V Students - DAS, RANJITA (SCHOOL SCIENCE, 2007)
CONCEPT LEARNING has been an important component of the teaching-learning process. Concepts are products of reasoning and once developed play an important role in further thinking. Children at all levels of development constantly learn situations. Poor understanding of concepts can lead to dead ends while their proper understanding can advance one’s comprehension of the subject.